The Thoughts of Nguyen Trai- A Vietnamese Statesman in the 15th Century - Chiêm, Nguyễn Thị (Tun Dr. Mahathir Mohamad Thoughts Institute (IPDM), 2017)
Nguyen Trai is one of the fourteen Vietnamese national heroes, a great thinker of the 15th century and one of the three Vietnamese world cultural celebrities. He made a major contribution to the literary production and thought system of Vietnam. His thought is found and systemized from his literary works by Vietnamese modern scholars. They are divided into principal fields involving national independence, military strategy and politics, philosophy as well as humanism and justice. All of these were influenced by Confucianism, Buddhism, Taoism and local patriotism. Vietnamese people see him as a bright example for the country’s younger generation. Some parts of his literary work are taught at schools. His life and work has become a source of inspiration for culture, art creation and academic research in Vietnam today. Keywords: Nguyen Trai, Vietnamese national heroes, national independence, humanism, patriotism, military strategy.